Malting Quality of ICARDA Elite Winter Barley (Hordeum vulgare L.) Germplasm Grown in Moroccan Middle Atlas - Bouhlal, Outmane; Raymond Affricot, Jean; Puglisi, Damiano; El-Baouchi, Adil; El Otmani, Fatima; Kandil, Mostafa; Hafidi, Abdellatif; Keser, Mesut; Sanchez-Garcia, Miguel; Visioni, Andrea (Taylor & Francis, 2022)
The use of barley (Hordeum vulgare L.) in Morocco is still limited to food and feed despite the amplified demand by local industries for imported malt. This study aims to evaluate 36 barley elite lines for major grain physicochemical parameters and malt quality traits. Analysis of variance, Pearson correlation, principal component analysis (PCA), and hierarchical cluster analysis (HCA) were performed. The results showed significant genotypic variation among genotypes for individual grain and malt traits. High broad sense heritability was obtained for all traits except for plump grain percentage, malt friability, and germination capacity. Starch, malt extract, Kolbach index, grain area, and test weight correlated significantly and negatively with barley protein. Malt extract correlated positively with Kolbach index and starch, but a negative correlation with soluble protein and malt protein was found. Based on 12 characters, 77% of the total genotypic variation was explained by the three first principal components following PCA and four clusters were depicted based on HCA. Genotypes of high interest with desirable levels of quality standards were identified to be used as a malt quality traits donor while designing crossing programs.